Interrelating the Breaking Strength of Novel Nano Tungsten Carbide Reinforced Aluminium Alloy Composites with Al-Mg-Cr Alloy (Journal of Pharmaceutical Negative Results, 2022)
Aim: In the present study an effort was made to synthesise Al-Mg-Cr alloy reinforced with nano WC tungsten carbide (WC) ceramic strengthening particles by stir casting was investigated, and it was compared to as-cast aluminium alloys in terms of compressive strength.Materials and Methods: Al-Mg-Cr alloy and 2wt% of novel nano tungsten carbide of particle size <50 nm was melted in a resisting heating furnace at 850°C with stirring speed of 500 rpm and stirring time 10 min respectively. The Al-Mg-Cr alloy nanocomposite was manufactured in two groups (Experiment =1 and Control Group =1). Sample sizes for each group were 20 with pre-test power of 80%, beta=0.05%, and CL 95%.Result:The Compressive strength and Yield strength of fabricated composites were analyzed from the results of the experiments and compared to the properties of as-cast Al-Mg-Cr alloy. The significance between the synthesized composites and the as-cast alloys was p=0.001(p<0.05). Conclusions: Within the limitations of this study, It was revealed that the compressive strength and yield strength of synthesized novel nano tungsten reinforced Al-Mg-Cr alloy composites significantly increased from 59.45% and 28% respectively owing to reduction in porosity and enhanced grain refinement between the intermixtures.